Pacific Northwest recipes - Orr, Tamra (Hockessin, Del. : Mitchell Lane Publishers, 2012)
Contains twenty-eight recipes unique to the Pacific Northwest, with step-by-step instructions and information about the region.
Includes bibliographical references (p. 60-61) and index.
6.9
5-8
Keywords: Cooking, American -- Pacific Northwest style -- Juvenile literature; Cooking, American; Cookbooks; Cooking; Cooking -- Juvenile literature